Flexible, Functional, and Familiar: Characteristics of SARS-CoV-2 Spike Protein Evolution - Saputri, Dianita S.; Li, Songling; van Eerden, Floris J.; Rozewicki, John; Xu, Zichang; Ismanto, Hendra S.; Davila, Ana; Teraguchi, Shunsuke; Katoh, Kazutaka; Standley, Daron M. (Frontiers in Microbiology, 2020)
The SARS-CoV-2 S protein is a major point of interaction between the virus and the human immune system. As a consequence, the S protein is not a static target but undergoes rapid molecular evolution. In order to more fully understand the selection pressure during evolution, we examined residue positions in the S protein that vary greatly across closely related viruses but are conserved in the subset of viruses that infect humans. These “evolutionarily important” residues were not distributed evenly across the S protein but were concentrated in two domains: the N-terminal domain and the receptor-binding domain, both of which play a role in host cell binding in a number of related viruses. In addition to being localized in these two domains, evolutionary importance correlated with structural flexibility and inversely correlated with distance from known or predicted host receptor-binding residues. Finally, we observed a bias in the composition of the amino acids that make up such residues toward more human-like, rather than virus-like, sequence motifs.